Recent advances in the biocatalytic mitigation of emerging pollutants: A comprehensive review - Ekeoma, Bernard Chukwuemeka; Ekeoma, Leonard Nnamdi; Yusuf, Mohammad; Haruna, Abdurrashid; Ikeogu, Chigozie Kosisochukwu; Merican, Zulkifli Merican Aljunid; Kamyab, Hesam; Pham, Cham Q.; Vo, Dai-Viet N.; Chelliapan, Shreeshivadasan (Journal of biotechnology, 2023)
The issue of environmental pollution has been worsened by the emergence of new contaminants whose morphology is yet to be fully understood . Several techniques have been adopted to mitigate the pollution effects of these emerging contaminants, and bioremediation involving plants, microbes, or enzymes has stood out as a cost-effective and eco-friendly approach. Enzyme-mediated bioremediation is a very promising technology as it exhibits better pollutant degradation activity and generates less waste. However, this technology is subject to challenges like temperature, pH, and storage stability, in addition to recycling difficulty as it is arduous to isolate them from the reaction media. To address these challenges, the immobilization of enzymes has been successfully applied to ameliorate the activity, stability, and reusability of enzymes. Although this has significantly increased the uses of enzymes over a wide range of environmental conditions and facilitated the use of smaller bioreactors thereby saving cost, it still comes with additional costs for carriers and immobilization. Additionally, the existing immobilization methods have their individual limitations. This review provides state-of-the-art information to readers focusing on bioremediation using enzymes. Different parameters such as: the sustainability of biocatalysts, the ecotoxicological evaluation of transformation contaminants, and enzyme groups used were reviewed. The efficacy of free and immobilized enzymes, materials and methods for immobilization, bioreactors used, challenges to large-scale implementation, and future research needs were thoroughly discussed. •Enzyme-based bioremediation is efficacious and cost-effective.•Immobilized enzymes though with its drawbacks are potentially better in bioremediation.•Materials and methods for enzyme immobilization play a crucial role in bioremediation.•Challenges of bioreactors regarding sustainability and scaling-up are discussed.•Future research for enzyme-mediated bioremediation was suggested.